2007
DOI: 10.1063/1.2724901
|View full text |Cite
|
Sign up to set email alerts
|

Imaging current flow in lobster nerve cord using the acoustoelectric effect

Abstract: Ultrasound traversing a biologic fluid or tissue generates a local change in electrical conductivity known as the acoustoelectric effect. The authors exploit this interaction to image ionic current injected into the abdominal segment of the lobster nerve cord. A pair of recording electrodes detected the acoustoelectric signal induced by pulses of focused ultrasound (1.4 or 7.5MHz). The signal was linear with injected current at 2MPa (0.7μV∕mAcm2) and pressure at 75mA∕cm2 (23μV∕MPa). Acoustoelectric imaging of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 9 publications
1
62
0
Order By: Relevance
“…2(c)), consistent with theory and previous studies. [4][5][6][7][8][9][10] Also, a gradual decrease in the AE signal was observed on distant recording electrodes ( Fig. 2(d)) relative to the ground reference.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2(c)), consistent with theory and previous studies. [4][5][6][7][8][9][10] Also, a gradual decrease in the AE signal was observed on distant recording electrodes ( Fig. 2(d)) relative to the ground reference.…”
mentioning
confidence: 99%
“…This complements earlier studies reporting that UCSDI has sufficient sensitivity to detect biologically relevant current in cardiac and neural tissue at safe levels of acoustic exposure for imaging. 4,5 The mechanical index (MI) is typically employed to quantify acoustic exposure for short ultrasound pulses at a low duty cycle. MI is defined as P neg /Hf c , where P neg is peak negative pressure and f c is center frequency in MHz.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acousto-Electric Interaction has been suggested as a technique for imaging the electrical conductivity distribution of biological tissues with a resolution typical of ultrasound [1], [2], [3], [4]. It has been shown that breast tumors have characteristic electrical properties different from those of healthy tissue [5].…”
Section: Introductionmentioning
confidence: 99%
“…7 Influential in the research of acousto-electric interaction signal in the recent years, has been a group of American researchers at the University of Michigan, that have performed several investigations on the AEI signal and the possibility of using the signal to map biological current. 2,[8][9][10][11][12][13][14][15][16][17] Several more studies have been performed for further investigations and improvements of measurements and setup. 18 Also our group has made some investigations and come up with a potentially useful application for denervated muscles.…”
Section: (2)mentioning
confidence: 99%